Interpreting Friendship and Betrayal in QS. Ali ‘Imrān [3]: 118: A Historical and Linguistic Analysis of Biṭānah and Min Dūnikum - Subaidah, Subaidah (Sunan Kalijaga Islamic State University, 2024)
The diversity of interpretations surrounding the prohibitive figure in QS. Ali ‘Imran [3]: 118, reflected in the terms biṭānah and min dūnikum as presented by various interpreters, carries the potential to foster exclusive behaviors within Muslim communities, especially in multi-religious regions. This study seeks to uncover the historical meaning intended in the verse to clarify the nature of this figure. Utilizing a qualitative approach, with the ma'nā-cum-maghzā method as an analytical tool, the research reveals that biṭānah refers to a close confidant who is granted access to personal information. Interpretations commonly align on this understanding, which contrasts with the term min dūnikum. The latter term is deeply embedded in its immediate context, pointing to a figure who lacks the same level of discretion or shared vision within a friendship. The divergence in vision leads to a potential for betrayal, prompting the verse to issue a caution regarding relationships with such individuals. This caution stems from the character of those who, not sharing the same vision, may harbor ill intentions, both physically and spiritually. The study concludes that the significance of min dūnikumlies not in religious identity but in the nature of the friendship, where differing visions can lead to a propensity for betrayal, even among members of the same community.